KINERJA BIDANG KESEHATAN DAN KELUARGA BERENCANA KABUPATEN BANYUASIN - Suripto, Suripto (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2011)
Government Regulation No. 38 of 2007 has been handed the assignment of government to local governments such as in health and family planning. Banyuasin District Government has conducted the affairs of the field very well. This is evidenced by the implementation of free healthprogram quality throughout the BanyuasinDistrict. Commitment to conduct free health quality is shown by means of improved facilities, health workers, among others, village health posts increased by 34 units, doctors increased by 24 people, midwives increased by 52 people, nurses increased by 71 peopleand public health graduates increased 35 people. Performance in the field of health and family planning has received appreciation and recognition nasinal. This review discusses the efficiency of development of health and family planning in the District Banyuasin.This is important because in the implementation of development in addition to using the principles of effectiveness but also efficiency. The method used in this study is evaluative method. In the analysis using Data Envelopment Analysis (DEA) model of Banker-Charnes-Cooper (BCC) with DEA-Solver software. The results show that the performance of district general Banyuasin at 0.99. This value indicates that the performance of health development has been relatively very efficient. efficiency in the administration of health and family planning in almost all districts in Banyuasin or has a value of 1:00 (one) and only salek water district that has a value of 0.83 (inefficient).